Desenvolvimento de uma metodologia para automatização dos processos de manobra em redes de distribuição de energia elétrica utilizando algoritmos evolutivos - Hunsche, Samuel (2021)
The present work approaches the Service Restoration Problem in electrical distribution networks. Therefore, a multi-objective evolutionary algorithm is developed considering the total de-energized load, the number of priority and non-priority customers de-energized, the number of switching operations and switching operations inside the clear area. Constraints as radiality, voltage limits and capacity of network elements are observed. A case study considering the maneuver time and fault duration as an alternative in choosing an efficient solution is developed. The representation of the electrical system graph is done using the characteristic vector modified to the correction of infeasible solutions, while the power flow is calculated using a sweeping method. Also, another approach considering the parallel processing of individuals from the population into different cores of the processor is tested. The methodology is implemented on the Matlab platform and tested on the 33, 69, 119 Bus test systems and on a real 1087 bus system.